Method for extracting lithium from lithium iron phosphate battery positive electrode waste material through piezoelectricity driving and capable of achieving magnetic circulation
In the wet recycling of the positive electrode waste of lithium iron phosphate battery, a piezoelectric driving method with magnetic cyclable piezoelectric catalytic reaction is used to drive the piezoelectric catalytic reaction using an ultrasonic device, and the selective extraction of lithium ions is achieved, solving the high cost and The problem of serious pollution has achieved efficient, low-cost and environmentally friendly lithium recycling.
Patent Information
- Application Number
- CN202411562152.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
Smart Images

Figure CN119461285A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to resource recovery of lithium iron phosphate battery positive electrode waste, and specifically to a magnetically cyclic piezoelectrically driven lithium iron phosphate battery positive electrode waste lithium extraction method. Background Art
[0002] Lithium-ion batteries have been widely used in many fields such as transportation and electronic equipment. Among them, lithium iron phosphate batteries have the advantages of low cost, good safety performance, long cycle life, and high theoretical capacity, and occupy a major market share of lithium batteries. However, after lithium iron phosphate batteries reach the end of their life cycle, they will face retirement and scrapping. If not properly disposed of, it will not only pose a serious threat to the ecological environment, but also greatly waste the valuable metal resources contained in the battery. Therefore, the recycling and resource utilization of retired lithium iron phosphate batteries will be a key issue directly related to metal strategic resources, carbon emission reduction of power batteries and sustainable development of the industry, and it has important practical significance for alleviating the energy crisis and protecting the ecological environment.
[0003] There are two common approaches to the treatment of waste positive electrodes of retired lithium iron phosphate batteries: direct repair and regeneration, and wet recycling. Among them: direct repair and regeneration is to compensate for the missing lithium elements of waste lithium iron phosphate materials after impurities are removed. However, in the case of large-scale waste treatment, the uniformity of lithium supplementation, the integrity of the battery structure, and the reproducibility of material performance cannot be guaranteed; wet recycling is to dissolve, leach and purify the metal elements of the positive electrode of the battery in a solution to obtain a usable product. Leaching, as the primary step of the wet process, plays a key role in the efficiency of lithium metal recovery. However, in the traditional acid leaching method, the reagent cost is high, the secondary pollution is serious, and there is not enough selectivity for the component elements, making the subsequent steps complicated and cumbersome. Therefore, it is urgent to find a metal leaching method for retired lithium iron phosphate battery positive electrode waste with high selectivity, high recovery rate, low cost, and green environmental protection to improve the efficiency of the entire wet recycling process. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a magnetically cyclic piezoelectrically driven method for extracting lithium from waste positive electrodes of lithium iron phosphate batteries, which can quickly and efficiently selectively extract lithium from waste positive electrodes of lithium iron phosphate batteries, thereby not only reducing production costs and improving lithium recovery efficiency, but also being environmentally friendly.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A magnetically cyclable piezoelectric driven lithium iron phosphate battery cathode waste lithium extraction method comprises the following steps:
[0007] Step 1: Add the positive electrode waste of lithium iron phosphate battery and bismuth ferrite with strong magnetic perovskite structure into deionized water, stir evenly, and use ultrasonic device to drive piezoelectric catalytic reaction. + Leaching into the solution, while Fe 2+ Oxidized to Fe 3+ And with PO4 3- Combine to form FePO4;
[0008] Step 2: After the piezoelectric reaction is completed, bismuth ferrite is firstly sucked out from the solution using a magnet, and then the solution is filtered to collect the reaction residue and the LiOH aqueous solution respectively.
[0009] Furthermore, the bismuth ferrite with perovskite structure having strong magnetism in step 1 is prepared by the following method:
[0010] Step 1.1, first take bismuth nitrate pentahydrate, ferric nitrate nonahydrate, deionized water and nitric acid with a mass fraction of 68% in the ratio of (1-1.1 mol): (1-1.1 mol): 200 mL: 20 mL respectively, then dissolve the ferric nitrate nonahydrate and bismuth nitrate pentahydrate in deionized water, then add nitric acid to the deionized water, and stir until the ferric nitrate nonahydrate and the bismuth nitrate pentahydrate are completely dissolved to obtain solution A;
[0011] Step 1.2, according to the molar ratio of bismuth nitrate pentahydrate to citric acid of 1: (1-1.5), add citric acid to solution A, stir until the solution turns yellow, and heat in an oil bath at 100° C. to obtain a viscous gel;
[0012] Step 1.3, drying the gel, then centrifuging and washing until the pH of the supernatant is neutral, and drying to obtain a powdered bismuth ferrite precursor;
[0013] Step 1.4, transfer the bismuth ferrite precursor to a porcelain boat and place it in a tube furnace, heat it from room temperature to 350-550°C at a heating rate of 5°C / min, and anneal it in an air atmosphere for 1-3h to obtain bismuth ferrite crystals with a perovskite structure having strong magnetism.
[0014] Furthermore, the drying in step 1.3 is performed in an oven at 150° C. for 2 to 3 hours.
[0015] Furthermore, the drying in step 1.3 is carried out at 60° C. for 24 hours.
[0016] Furthermore, in the step 1, the ratio of the lithium iron phosphate battery positive electrode waste, the perovskite structure bismuth ferrite with strong magnetism and the deionized water is (0.1-1g): (0.2-0.4g): 1L.
[0017] Furthermore, the ultrasonic device in step 1 is a low-frequency ultrasonic cleaner with an ultrasonic frequency of 40 kHz and a power of 300 W.
[0018] Furthermore, the temperature of the piezoelectric catalytic reaction in step 1 is 20±2°C.
[0019] Compared with the prior art, the present invention has the following technical effects:
[0020] The present invention is based on the leaching process in the wet recycling process of retired lithium iron phosphate batteries, combined with piezoelectric catalytic reaction, and proposes an oxidation selective lithium extraction technology. Since the perovskite structure bismuth ferrite with strong magnetism exhibits a large spontaneous polarization and a high piezoelectric coefficient at room temperature, it exhibits a strong piezoelectric effect under the external force driving of the ultrasonic device, triggering a piezoelectric catalytic reaction, which makes the Li in the LiFePO4 lattice + Specifically, bismuth ferrite, a piezoelectric crystal material with an asymmetric center, is squeezed or stretched and subjected to stress, and the lattice atoms are offset from their original positions to produce an electric dipole moment, generating a piezoelectric potential inside the crystal, resulting in a net positive and negative charge on the opposite outer surface of the crystal. The positive and negative charges undergo a redox reaction with oxygen molecules or water molecules in the ambient medium to generate an oxidant, H2O2. The oxidizing property of H2O2 is used to convert Fe in LiFePO4 to 2+ Oxidized to Fe 3+ And with PO4 3- The combination is precipitated in the form of FePO4, and the metallic lithium is precipitated in the form of Li + In the form of leaching from the LiFePO4 lattice and into the solution, the reaction process of leaching lithium ions by oxidation with H2O2 is: 2LiFePO4+H2O2→2LiOH+2FePO4, realizing a one-step oxidation selective lithium extraction process from the positive electrode waste of lithium iron phosphate batteries, achieving the purpose of selective separation of Li and Fe. In addition, with the help of the strong magnetism of bismuth ferrite, it can be separated from the reaction solution by a magnet for subsequent recycling. In short, the present invention utilizes ultrasound-driven piezoelectric catalytic reaction to quickly and efficiently selectively extract lithium from the positive electrode waste of lithium iron phosphate batteries, which not only has a high recovery rate, but also is low-cost, green and environmentally friendly, and improves the wet recovery efficiency of retired lithium iron phosphate batteries.
[0021] As a typical piezoelectric material, bismuth ferrite has excellent properties such as high spontaneous polarization, high Curie temperature, strong magnetoelectric coupling and low band gap. BiFeO3 with different structures has different properties. The present invention prepares BiFeO3 with perovskite structure by reasonably controlling process parameters and raw material ratio. The BiFeO3 has ferroelectricity and antiferromagnetism. Its ferroelectricity mainly comes from Bi6s 2The orbital hybridization between O2p and FeO6 can drive the FeO6 octahedron to produce lattice distortion along the (111) crystal plane, resulting in the separation of positive and negative charge centers in the lattice, so that BiFeO3 exhibits a large spontaneous polarization and a high piezoelectric coefficient at room temperature, and exhibits a strong piezoelectric effect under the action of external force, thereby inducing a piezoelectric catalytic reaction; in addition, the BiFeO3 prepared by the present invention is accompanied by magnetic / electric coupling characteristics, and has very broad application prospects in magnetoelectric coupling, electromechanical coupling, photoelectric effect, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : X-ray diffraction pattern of bismuth ferrite prepared in Example 1 of the present invention;
[0023] Figure 2 : SEM image of bismuth ferrite prepared in Example 1 of the present invention;
[0024] Figure 3 : Piezoelectric force microscope image of bismuth ferrite prepared in Example 1 of the present invention;
[0025] Figure 4 : The curve of the change of hydrogen peroxide content generated by piezoelectric catalysis over time in Example 1 of the present invention;
[0026] Figure 5 : Curve of the change of lithium ion and iron ion leaching rate over time during the piezoelectric catalytic reaction of Example 1 of the present invention;
[0027] Figure 6 : The bar graph of the leaching rate of lithium ions and iron ions after 8 hours of piezoelectric catalytic reaction in Examples 1 to 4 of the present invention;
[0028] Figure 7 : Histogram of lithium ion and iron ion leaching rates after 8 hours of piezoelectric catalytic reaction in Comparative Example 1, Example 5 and Example 6 of the present invention;
[0029] Figure 8 : Photograph of magnetic recovery of bismuth ferrite after the piezoelectric catalytic reaction in Example 1 of the present invention;
[0030] Fig. 9 : hysteresis loop spectrum of bismuth ferrite prepared in Example 1 of the present invention;
[0031] Fig.10 : XRD diagram of the reaction slag after the piezoelectric catalytic reaction in Example 1 of the present invention is completed. DETAILED DESCRIPTION
[0032] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0033] The lithium iron phosphate battery positive electrode powder selected in Examples 1 to 8 and Comparative Example 1 contains 44 mg of lithium and 355 mg of iron per gram of lithium iron phosphate battery positive electrode waste.
[0034] Example 1
[0035] Step 1: preparing bismuth ferrite with a perovskite structure having strong magnetism, comprising the following steps:
[0036] Step 1.1, first take 19.4g of bismuth nitrate pentahydrate and 16.16g of ferric nitrate nonahydrate according to a molar ratio of 1:1, then dissolve the ferric nitrate nonahydrate and bismuth nitrate pentahydrate in 200mL of deionized water, then add 20mL of nitric acid with a mass fraction of 68% to the deionized water, and stir until the ferric nitrate nonahydrate and bismuth nitrate pentahydrate are completely dissolved to obtain solution A;
[0037] Step 1.2, according to the molar ratio of bismuth nitrate pentahydrate to citric acid of 1:1, add citric acid to solution A, stir until the solution turns yellow, and heat in an oil bath at 100° C. until no obvious liquid is visible, to obtain a viscous gel;
[0038] Step 1.3, transfer the gel to a watch glass and place it in an oven at 150°C for 2 hours, then centrifuge and wash until the pH of the supernatant is neutral, and dry it at 60°C for 24 hours to obtain a powdered bismuth ferrite precursor;
[0039] Step 1.4, transferring the bismuth ferrite precursor to a porcelain boat and placing it in a tube furnace, heating the temperature from room temperature to 450°C at a heating rate of 5°C / min, and annealing in an air atmosphere for 2 hours to obtain a bismuth ferrite crystal with a perovskite structure having strong magnetism;
[0040] Step 2: Add 5 mg of lithium iron phosphate battery positive electrode waste and 10 mg of bismuth ferrite with strong magnetic perovskite structure into 50 mL of deionized water, stir evenly, and drive the piezoelectric catalytic reaction for 8 hours at 20°C using a low-frequency ultrasonic cleaner with an ultrasonic frequency of 40 kHz and a power of 300 W to make the Li in the LiFePO4 lattice + Leaching into the solution to form LiOH, while Fe 2+ Oxidized to Fe 3+ And with PO4 3- Combine to form FePO4;
[0041] Step 3: After the piezoelectric reaction is completed, bismuth ferrite is firstly sucked out from the solution using a magnet, and then the solution is filtered to collect the reaction residue FePO4 and the LiOH aqueous solution respectively.
[0042] from Figure 1It can be seen from the X-ray diffraction pattern of bismuth ferrite that the main diffraction peak of bismuth ferrite prepared in Example 1 is completely consistent with the diffraction peak of the standard card PDF 86-1518 of bismuth ferrite with perovskite structure, indicating that step 1 successfully prepared bismuth ferrite with perovskite structure.
[0043] from Figure 2 It can be seen from the SEM image of bismuth ferrite that the bismuth ferrite prepared in Example 1 is composed of agglomerated spherical particles.
[0044] from Figure 3 It can be seen from the piezoelectric force microscope image of bismuth ferrite that the zigzag curve of the triangular points shows that the bismuth ferrite synthesized in Example 1 has the domain reversal characteristics of ferroelectric materials, while the pentagonal butterfly-shaped curve shows that the bismuth ferrite material prepared in Example 1 has significant piezoelectric properties.
[0045] During the piezoelectric reaction in step 2, the hydrogen peroxide content in the solution was measured at 0 h, 2 h, 4 h, 6 h and 8 h using the iodination method. The results are as follows: Figure 4 As shown, the maximum absorption wavelength is reached at 352 nm, and the cumulative amount of hydrogen peroxide increases with the extension of reaction time, indicating that the oxidant H2O2 is generated after the piezoelectric reaction starts.
[0046] During the piezoelectric reaction of step 2 of Example 1, the contents of lithium ions and iron ions in the solution were measured at 0 h, 2 h, 4 h, 6 h and 8 h, respectively. The results are as follows: Figure 5 As shown, it can be seen that with the extension of reaction time, the leaching efficiency of lithium ions gradually increases. After 8 hours of reaction, the extraction rate of lithium ions reaches 82.55%, while the leaching efficiency of iron ions remains at a low level. Even after 8 hours of reaction, the leaching rate of iron ions is only 0.06%. The entire piezoelectric reaction process shows an excellent selective lithium extraction effect, indicating that the piezoelectric catalysis of bismuth ferrite material can selectively extract lithium from the positive electrode waste of lithium iron phosphate batteries.
[0047] After the piezoelectric reaction of Example 1 is completed, a magnet is attached to the wall of the glass container to absorb bismuth ferrite from the solution. The results are as follows: Figure 8 As shown, the brown bismuth ferrite is absorbed to the inner side of the container wall, and the gray reaction residue settles to the bottom of the bottle, indicating that the strong magnetic catalyst bismuth ferrite and the reaction residue can be successfully separated by magnet.
[0048] from Fig. 9 It can be seen from the hysteresis loop spectrum of bismuth ferrite that the saturation magnetization intensity of bismuth ferrite prepared in Example 1 is 8emu / g, indicating that it has strong magnetism.
[0049] After drying the reaction slag collected in step 3 of Example 1, XRD characterization was performed on it. The results are as follows: Fig.10As shown, it can be seen that the diffraction peak of the reaction slag is completely consistent with the diffraction peak of FePO4, indicating that the main component of the reaction slag is iron phosphate FePO4.
[0050] Example 2
[0051] The only difference from Example 1 is that in step 2, the amount of lithium iron phosphate battery positive electrode waste is 15 mg.
[0052] Example 3
[0053] The only difference from Example 1 is that the amount of lithium iron phosphate battery positive electrode waste in step 2 is 25 mg.
[0054] Example 4
[0055] The only difference from Example 1 is that in step 2, the amount of lithium iron phosphate battery positive electrode waste is 50 mg.
[0056] Example 5
[0057] The only difference from Example 1 is that in step 2, the amount of bismuth ferrite with a perovskite structure having strong magnetism is 10 mg.
[0058] Example 6
[0059] The only difference from Example 1 is that in step 2, the amount of bismuth ferrite with a perovskite structure having strong magnetism is 20 mg.
[0060] Example 7
[0061] Step 1: preparing bismuth ferrite with a perovskite structure having strong magnetism, comprising the following steps:
[0062] Step 1.1, first take 21.34g of bismuth nitrate pentahydrate and 16.16g of ferric nitrate nonahydrate according to a molar ratio of 1.1:1, then dissolve the ferric nitrate nonahydrate and bismuth nitrate pentahydrate in 200mL of deionized water, then add 20mL of nitric acid with a mass fraction of 68% to the deionized water, and stir until the ferric nitrate nonahydrate and bismuth nitrate pentahydrate are completely dissolved to obtain solution A;
[0063] Step 1.2, according to the molar ratio of bismuth nitrate pentahydrate to citric acid of 1:1.3, citric acid was added to solution A, stirred until the solution turned yellow, and heated in an oil bath at 100° C. until no obvious liquid was visible, to obtain a viscous gel;
[0064] Step 1.3, transfer the gel to a watch glass and place it in an oven at 150°C for 3 hours, then centrifuge and wash until the pH of the supernatant is neutral, and dry it at 60°C for 24 hours to obtain a powdered bismuth ferrite precursor;
[0065] Step 1.4, transferring the bismuth ferrite precursor to a porcelain boat and placing it in a tube furnace, heating the temperature from room temperature to 350° C. at a heating rate of 5° C. / min, and annealing in an air atmosphere for 3 h to obtain a bismuth ferrite crystal with a perovskite structure having strong magnetism;
[0066] Step 2: Add 5 mg of lithium iron phosphate battery positive electrode waste and 10 mg of bismuth ferrite with strong magnetic perovskite structure into 50 mL of deionized water, stir evenly, and drive the piezoelectric catalytic reaction for 8 hours at 18 ° C using a low-frequency ultrasonic cleaner with an ultrasonic frequency of 40 kHz and a power of 300 W to make the Li in the LiFePO4 lattice + Leaching into the solution, while Fe 2+ Oxidized to Fe 3 + And with PO4 3- Combine to form FePO4;
[0067] Step 3: After the piezoelectric reaction is completed, bismuth ferrite is firstly sucked out from the solution using a magnet, and then the solution is filtered to collect the reaction residue FePO4 and the LiOH aqueous solution respectively.
[0068] Example 8
[0069] Step 1: preparing bismuth ferrite with a perovskite structure having strong magnetism, comprising the following steps:
[0070] Step 1.1, first take 19.4g of bismuth nitrate pentahydrate and 17.78g of ferric nitrate nonahydrate according to a molar ratio of 1:1.1, then dissolve the ferric nitrate nonahydrate and bismuth nitrate pentahydrate in 200mL of deionized water, then add 20mL of nitric acid with a mass fraction of 68% to the deionized water, and stir until the ferric nitrate nonahydrate and bismuth nitrate pentahydrate are completely dissolved to obtain solution A;
[0071] Step 1.2, according to the molar ratio of bismuth nitrate pentahydrate to citric acid of 1:1.5, citric acid was added to solution A, stirred until the solution turned yellow, and heated in an oil bath at 100° C. until no obvious liquid was visible, to obtain a viscous gel;
[0072] Step 1.3, transfer the gel to a watch glass and place it in an oven at 150°C for 3 hours, then centrifuge and wash until the pH of the supernatant is neutral, and dry it at 60°C for 24 hours to obtain a powdered bismuth ferrite precursor;
[0073] Step 1.4, transferring the bismuth ferrite precursor to a porcelain boat and placing it in a tube furnace, heating the temperature from room temperature to 550° C. at a heating rate of 5° C. / min, and annealing in an air atmosphere for 1 h to obtain a bismuth ferrite crystal with a perovskite structure having strong magnetism;
[0074] Step 2: Add 5 mg of lithium iron phosphate battery positive electrode waste and 10 mg of bismuth ferrite with strong magnetic perovskite structure into 50 mL of deionized water, stir evenly, and drive the piezoelectric catalytic reaction for 8 hours at 22 ° C using a low-frequency ultrasonic cleaner with an ultrasonic frequency of 40 kHz and a power of 300 W to make the Li in the LiFePO4 lattice + Leaching into the solution, while Fe 2+ Oxidized to Fe 3 + And with PO4 3- Combine to form FePO4;
[0075] Step 3: After the piezoelectric reaction is completed, bismuth ferrite is firstly sucked out from the solution using a magnet, and then the solution is filtered to collect the reaction residue FePO4 and the LiOH aqueous solution respectively.
[0076] Comparative Example 1
[0077] The only difference from Example 1 is that the amount of bismuth ferrite with a perovskite structure having strong magnetism in step 2 is 0 mg.
[0078] After the piezoelectric reaction in step 2 of comparative example 1 and embodiment 1 to embodiment 6 was carried out for 8 hours, the contents of lithium ions and iron ions in the solution were respectively measured, and the leaching rates of lithium ions and iron ions were calculated. The results are as follows: Figure 6 and Figure 7 Shown: From Figure 6 It can be seen that when the addition amount of bismuth ferrite in Examples 1 to 4 is always 10 mg, the leaching rate of lithium ions in the solution decreases with the increase of the positive electrode waste content of the lithium iron phosphate battery (i.e., the solid-liquid ratio in the figure), and the leaching rate of iron ions does not change much; Figure 7 It can be seen that when the addition amount of the positive electrode waste of the lithium iron phosphate battery in Comparative Example 1, Example 5 and Example 6 is always 5 mg, the leaching rate of lithium ions in the solution increases with the increase of the addition amount of the catalyst bismuth ferrite. Specifically, in Comparative Example 1, when bismuth ferrite is not added, only ultrasonic vibration is used to trigger the piezoelectric reaction, and the leaching rate of lithium ions in the solution is only 41.88%, and the leaching rate of iron ions is 0.33%; in Example 5 and Example 6, when 10 mg and 20 mg of bismuth ferrite are added respectively, the leaching rates of lithium ions reach 82.55% and 87.58%, respectively, and the leaching rates of iron ions are reduced to 0.06% and 0.07%, respectively, indicating that the introduction of bismuth ferrite in the piezoelectric reaction process can effectively improve the selectivity and leaching effect of lithium ions.
Claims
1. A magnetically cyclic piezoelectric driven lithium iron phosphate battery cathode waste lithium extraction method, characterized in that: The steps include: Step 1: Add the positive electrode waste of lithium iron phosphate battery and bismuth ferrite with strong magnetic perovskite structure into deionized water, stir evenly, and use ultrasonic device to drive piezoelectric catalytic reaction. + Leaching into the solution, while Fe 2+ Oxidized to Fe 3+ And with PO4 3- Combine to form FePO4; Step 2: After the piezoelectric reaction is completed, bismuth ferrite is firstly sucked out from the solution using a magnet, and then the solution is filtered to collect the reaction residue and the LiOH aqueous solution respectively.
2. The method for extracting lithium from waste positive electrode of a piezoelectrically driven lithium iron phosphate battery capable of magnetic circulation according to claim 1, characterized in that: The bismuth ferrite with perovskite structure having strong magnetism in step 1 is prepared by the following method: Step 1.1, first take bismuth nitrate pentahydrate, ferric nitrate nonahydrate, deionized water and nitric acid with a mass fraction of 68% in the ratio of (1-1.1 mol): (1-1.1 mol): 200 mL: 20 mL respectively, then dissolve the ferric nitrate nonahydrate and bismuth nitrate pentahydrate in deionized water, then add nitric acid to the deionized water, and stir until the ferric nitrate nonahydrate and the bismuth nitrate pentahydrate are completely dissolved to obtain solution A; Step 1.2, according to the molar ratio of bismuth nitrate pentahydrate to citric acid of 1: (1-1.5), add citric acid to solution A, stir until the solution turns yellow, and heat in an oil bath at 100° C. to obtain a viscous gel; Step 1.3, drying the gel, then centrifuging and washing until the pH of the supernatant is neutral, and drying to obtain a powdered bismuth ferrite precursor; Step 1.4, transfer the bismuth ferrite precursor to a porcelain boat and place it in a tube furnace, heat it from room temperature to 350-550°C at a heating rate of 5°C / min, and anneal it in an air atmosphere for 1-3h to obtain bismuth ferrite crystals with a perovskite structure having strong magnetism.
3. The method for extracting lithium from waste positive electrode of a piezoelectrically driven lithium iron phosphate battery capable of magnetic circulation according to claim 2, characterized in that: The drying in step 1.3 is performed in an oven at 150° C. for 2 to 3 hours.
4. The method for extracting lithium from waste positive electrode of a piezoelectric-driven lithium iron phosphate battery capable of magnetic circulation according to claim 2, characterized in that: The drying in step 1.3 is carried out at 60° C. for 24 hours.
5. The method for extracting lithium from waste positive electrode of a piezoelectric driven lithium iron phosphate battery capable of magnetic circulation according to claim 1, characterized in that: In the step 1, the ratio of the lithium iron phosphate battery positive electrode waste, the perovskite structure bismuth ferrite with strong magnetism and the deionized water is (0.1-1g): (0.2-0.4g): 1L.
6. The method for extracting lithium from waste positive electrode of a piezoelectric driven lithium iron phosphate battery capable of magnetic circulation according to claim 1, characterized in that: The ultrasonic device in step 1 is a low-frequency ultrasonic cleaner with an ultrasonic frequency of 40 kHz and a power of 300 W.
7. The method for extracting lithium from waste positive electrode of a piezoelectric driven lithium iron phosphate battery capable of magnetic circulation according to claim 1, characterized in that: The temperature of the piezoelectric catalytic reaction in step 1 is 20±2°C.